Extension of the growing season increases vegetation exposure to frost - Qiang Liu (Nature Portfolio, 2018)
Plant growing season increases under a warming climate, but it is not known whether this will alter plant exposure to frost days. Here Liu et al. investigate trends in the Northern Hemisphere over 30 years and find increased exposure to frost days in regions that have longer growing seasons.